2022
DOI: 10.25273/linguista.v6i1.13056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of direct corrective feedback on writing an Undergraduate Thesis

Abstract: <p class="AbstractText"><em>This study explored the use of direct corrective feedback in the Thesis Proposal writing course where the students are expected to develop their undergraduate thesis proposal at Universitas Brawijaya and how direct corrective feedback can help the students to deal with their academic writing. The data were obtained from six students who have taken the Thesis Proposal Writing course and one lecturer who taught the course using two instruments: an interview guide and obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The results showed that feeling overwhelmed becomes the highest one due to the number of students followed by plagiarism and how the students organize their ideas. This result is in line with [25], [26] Anyiedah (2017), and [27] in terms of the number of students, but it differs from the other factors which are students" proficiency and time constraint. However, it is in contrast to [28] and Singh, et al (2020) who found that sufficient training, pedagogical knowledge, and qualification are the challenges for the teacher, [29] , Hidayati (2018), [30], Rasid & Hui (2021) who found that motivating students, different range of proficiency, parental involvement, and lack of knowledge are the challenge to teach writing.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that feeling overwhelmed becomes the highest one due to the number of students followed by plagiarism and how the students organize their ideas. This result is in line with [25], [26] Anyiedah (2017), and [27] in terms of the number of students, but it differs from the other factors which are students" proficiency and time constraint. However, it is in contrast to [28] and Singh, et al (2020) who found that sufficient training, pedagogical knowledge, and qualification are the challenges for the teacher, [29] , Hidayati (2018), [30], Rasid & Hui (2021) who found that motivating students, different range of proficiency, parental involvement, and lack of knowledge are the challenge to teach writing.…”
Section: Discussionsupporting
confidence: 82%
“…It is another essential factor that can affect both teachers and students in the teaching and learning writing process. For example, [27] mentioned that sometimes the teacher felt afraid and worried about providing feedback due to the effect after the students receive feedback and [41] found that low achiever students suddenly became demotivated and discouraged with direct teacher feedback.…”
Section: Discussionmentioning
confidence: 99%